Applying the Information–Motivation–Behavioral Skills model to a video-assisted HPV intervention to promote self-screening uptake: a qualitative study in Western Kenya - Michelle Huang; Hanul Choi; Haley Dion; Laya Sathyan; Emily Herfel; Breandan Makhulo; Jeniffer Ambaka; Megan J. Huchko (BMJ Global Health)
Introduction Human papillomavirus (HPV) is the leading source of cervical cancer in Kenya. HPV, like other sexually transmitted infections, is stigmatised, which hinders efforts to address the disease. Education and empowerment are crucial in combating HPV stigma and increasing screening uptake. We conducted qualitative analyses of a video-assisted HPV educational intervention in Kisumu, Kenya to determine its impact on women’s knowledge, motivation and behaviour for HPV and cervical cancer prevention. The stigma-responsive video featured a group discussion with an individual describing her experience with HPV, self-testing and preventive treatment.Methods Three focus group discussions (FGDs) were conducted with 10 women, respectively, ages 30–64, from three intervention clinics, to explore their experience with the video-assisted education, perspectives on HPV and self-sampling, and the feasibility of peer-led education to increase screening and follow-up. The initial codebook was developed prior to the FGDs using an Information–Motivation–Behavioral (IMB) Skills model framework, followed by a rapid analysis to identify missing themes. We conducted qualitative coding using NVivo V.12. The IMB Skills model was used to analyse the codes and findings from the FGDs to assess the impact of the education.Result Women in FGDs identified the lack of community-level knowledge on HPV and the stigma and fear of physical pain from pelvic examination as barriers to HPV screening. Many participants mentioned that the knowledge gained through the video reduced their stigma and fear, and it motivated them to screen. Participants demonstrated behavioural change through self-sampling uptake, community empowerment and referral to watch the video.Conclusion From the FGDs, we found the direct mechanism linking information, motivation and screening behaviour in our video-assisted HPV educational intervention. The intervention improved women’s self-reported HPV-related knowledge and increased their motivation for self-sampling and engagement in preventive behaviours. We recommend scaling up the intervention by bringing the video-assisted education to more clinics in Kisumu.